2020
DOI: 10.3390/biom10010147
|View full text |Cite
|
Sign up to set email alerts
|

Combined Kinetin and Spermidine Treatments Ameliorate Growth and Photosynthetic Inhibition in Vigna angularis by Up-Regulating Antioxidant and Nitrogen Metabolism under Cadmium Stress

Abstract: Pot experiments were conducted to investigate the probable beneficial role of the individual as well as combined application of kinetin (50 μM Kn) and spermidine (200 μM Spd) on Vigna angularis under cadmium (Cd) stress. Cd treatment reduced growth by declining the content of chlorophylls and carotenoids, photosynthesis, and gas exchange parameters. Exogenously, Kn and Spd application enhanced the photosynthetic parameters and up-regulated the antioxidant system by improving the activities of antioxidant enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 75 publications
10
36
0
Order By: Relevance
“…Cytokinins (CKs) for example, take part in numerous physiological activities such as cell division and morphogenesis, flower and seed development and chloroplast development [12][13][14][15][16]. CKs can also regulate the abiotic stresses by the up-regulation of nitrogen metabolism and antioxidant defense system of plants [12,[17][18][19][20][21]; the importance of CKs in the regulation of heavy metal stress tolerance in plants is well known [11,17,18,22], but the mechanism of CKs induced regulation of heavy metal stress tolerance needs further investigation. The work reported here aimed to determine the effect of exogenous application of different level of KN (KN L , KN M and KN H ) on Trigonella seedlings (in order to counteract Cd phyto-toxicity) by examining their effects on growth and photochemistry of the PS II and AsA-GSH cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins (CKs) for example, take part in numerous physiological activities such as cell division and morphogenesis, flower and seed development and chloroplast development [12][13][14][15][16]. CKs can also regulate the abiotic stresses by the up-regulation of nitrogen metabolism and antioxidant defense system of plants [12,[17][18][19][20][21]; the importance of CKs in the regulation of heavy metal stress tolerance in plants is well known [11,17,18,22], but the mechanism of CKs induced regulation of heavy metal stress tolerance needs further investigation. The work reported here aimed to determine the effect of exogenous application of different level of KN (KN L , KN M and KN H ) on Trigonella seedlings (in order to counteract Cd phyto-toxicity) by examining their effects on growth and photochemistry of the PS II and AsA-GSH cycles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cd stress (100 µM CdCl 2 ) resulted in increased MDA and H 2 O 2 in Arabidopsis thaliana [ 103 ] and Cucumis sativus seedlings [ 104 ]. In a recent study, Ahanger et al [ 105 ] reported that lipid peroxidation, EL, H 2 O 2 , and O 2 •− contents as well as LOX activity were markedly increased in V. angularis seedlings under Cd stress (100 µM CdCl 2 , 20 d), while a similar increase in EL, H 2 O 2 and TBARS contents was recorded in Mentha arvensis under Cd stress (50 µM CdCl 2 , 100 d) [ 106 ]. Hasanuzzaman et al [ 107 ] demonstrated higher MDA, H 2 O 2 , and O 2 •− content in wheat plants subjected to lead (Pb) stress (0.5 and 1.0 mM Pb(NO 3 ) 2 ) compared with control.…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 99%
“…Moreover, Ni stress-induced enhancement of SOD, GPX, APX, MDHAR, DHAR, and GR activities, which was further upregulated by Si supplementation that helped to minimize Ni toxicity. Ahanger et al [ 105 ] reported an increment in GSH and tocopherol content along with SOD, GST, and DHAR activities with higher H 2 O 2 (61%) and O 2 •− (47%) content in Cd-stressed (100 µM CdCl 2 , 20 d) V. angularis seedlings, whereas AsA levels and CAT activity declined. Contrarily, SOD, CAT, POX, and GR activities were upregulated with higher content of H 2 O 2 (53.45% and 69.83%, respectively) under Cd stress (50 µM CdCl 2 , 100 d) in two Mentha arvensis (cv.…”
Section: Antioxidant Defense In Plants Under Abiotic Stress: Recenmentioning
confidence: 99%
“…But, the inappropriate application of fertilizers, drastically disturbs the soil ecosystem and increases heavy metal intoxication ( Ozturk et al, 2011 , Saini et al, 2019a ). Pb, Cd, Ni and Cr are the significant elements present in fertilizers and pesticides can cause biomagnification, out of which Pb and Cd are toxic to potato plant and humans upon consumption even at low concentration ( John et al, 2009 , Bali et al, 2018 , Bali et al, 2019a , Bali et al, 2019b , Jan et al, 2018 , Kaur et al, 2017 , Kaya et al, 2020a , Kaya et al, 2020b , Kaya et al, 2020c , Ahanger et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%